Central Sensitization in Chronic Musculoskeletal Pain Disorders in Different Populations: A Cross-Sectional Study. Issue 11 (31st March 2020) - Roldán-Jiménez, Cristina; Pérez-Cruzado, David; Neblett, Randy; Gatchel, Robert; Cuesta-Vargas, Antonio
Abstract: Objective: Chronic musculoskeletal pain disorders (CMPDs) are among the leading causes of disabilities across populations, resulting in high social and financial burden. This persistent pain condition may include the central sensitization (CS) phenomenon, which implies a wide range of symptoms and that may be taken into account in CMPD treatment. CS symptoms can be measured by the Central Sensitization Inventory (CSI). The aims of the study were to describe CS symptoms in patients suffering from several CMPDs and to analyze differences due to gender, age, and body mass index (BMI). Design: This cross-sectional study recruited a total of 395 Spanish participants suffering from several CMPDs. Setting: CS symptoms were measured with the Spanish Version of the CSI. The total score (0–100) and a cutoff score of 40 were recorded. Subjects: A total of 395 participants were included. Results: The mean CSI total score for the whole sample was 24.6 ± 12.0 points. CSI total score had subclinical values in the whole sample, whereas participants with scores >40 were found across different CMPDs, such as low back pain (37.8%) and neck pain (32.4%); 14.6% of females and 1.7% of males presented CSI scores >40. Patients showed significant differences in CSI cutoff point by gender ( P = 0.010) and CSI total score by age ( P = 0.014). Conclusions: Given the high prevalence of clinically relevant CSI scores (>40) in people with a CMPD, especially low back pain and neck pain, we recommend that clinicians supplement their assessment with the CSI for improved decision-making during treatment.